Prison tobacco control policies and deaths from smoking in United States prisons: population based retrospective analysis - Binswanger, Ingrid A (BMJ Publishing Group Ltd., 2014)
Objective To determine the mortality attributable to smoking and years of potential life lost from smoking among people in prison and whether bans on smoking in prison are associated with reductions in smoking related deaths. Design Analysis of cross sectional survey data with the smoking attributable mortality, morbidity, and economic costs system; population based time series analysis. Setting All state prisons in the United States. Main outcome measures Prevalence of smoking from cross sectional survey of inmates in state correctional facilities. Data on state prison tobacco policies from web based searches of state policies and legislation. Deaths and causes of death in US state prisons from the deaths in custody reporting program of the Bureau of Justice Statistics for 2001-11. Smoking attributable mortality and years of potential life lost was assessed from the smoking attributable mortality, morbidity, and economic costs system of the Centers for Disease Control and Prevention. Multivariate Poisson models quantified the association between bans and smoking related cancer, cardiovascular and pulmonary deaths. Results The most common causes of deaths related to smoking among people in prison were lung cancer, ischemic heart disease, other heart disease, cerebrovascular disease, and chronic airways obstruction. The age adjusted smoking attributable mortality and years of potential life lost rates were 360 and 5149 per 100 000, respectively; these figures are higher than rates in the general US population (248 and 3501, respectively). The number of states with any smoking ban increased from 25 in 2001 to 48 by 2011. In prisons the mortality rate from smoking related causes was lower during years with a ban than during years without a ban (110.4/100 000 v 128.9/100 000). Prisons that implemented smoking bans had a 9% reduction (adjusted incidence rate ratio 0.91, 95% confidence interval 0.88 to 0.95) in smoking related deaths. Bans in place for longer than nine years were associated with reductions in cancer mortality (adjusted incidence rate ratio 0.81, 95% confidence interval 0.74 to 0.90). Conclusions Smoking contributes to substantial mortality in prison, and prison tobacco control policies are associated with reduced mortality. These findings suggest that smoking bans have health benefits for people in prison, despite the limits they impose on individual autonomy and the risks of relapse after release.